SARS-CoV-2 infection dynamics in the tourism season 2020 in North Frisia, Germany - Greiner, Timo; Aigner, Annette; Tinnemann, Peter (Frontiers in Epidemiology, 2022)
Background: International tourist activities including air travel, holiday on cruise ships, and Après-ski parties played a prominent role in the early spread of the SARS-CoV-2 pandemic. However, the effects of national tourism on infection dynamics are unclear. Methods: Data were analyzed from the health authorities in North Frisia, the northernmost district in Germany with prominent tourist hotspots such as Sylt, Amrum, and Föhr. Data were available for the time period April 2020 to November 2020. Results: During the tourist season (May to October 2020), PCR-confirmed SARS-CoV-2 case numbers were low with 0 to 10 cases per day. Case numbers rose in September and peaked end of October (2nd wave). Among the confirmed cases, 13 persons were returning travelers and none were national tourists. Overall, only a small proportion of cases were related to individuals with presumed tourist contact. Conclusion: In summer 2020, the arrival of a large number of tourists did not increase local case numbers, and tourism-related outbreaks were not reported. Thus, tourism did not contribute substantially to SARS-CoV-2 infection dynamics in North Frisia. However, incidences were low countrywide and protective measures were in place.